(untitled) (Medicine Today, 2016)
Ventricular shunts are commonly employed in the management of hydrocephalus, Numerous complications such as dissection, migration and malfunction have been reported in the literature. Here we present a case of migration of the peritoneal catheter through anus who attended in our institute. He was managed successfully without further complications. Medicine Today 2015 Vol.27(2): 44-45